1999
DOI: 10.1007/s002530051545
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of water-polluting sulfonoaromatic compounds

Abstract: Highly substituted arenesulfonates are chemically stable compounds with a range of industrial applications, and they are widely regarded as being poorly degradable. We did enrichment cultures for bacteria able to utilise the sulfonate moiety of 14 compounds, and we obtained mixed cultures that were able to desulfonate each compound. The products formed were usually identi®ed as the corresponding phenol, but because we could not obtain pure cultures, we followed up these ®ndings with quantitative work in pure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Ruff and co-workers showed that fourteen sulfonated aromatic compounds, five of which were sulfonated aromatic amines, were degraded by a mixed culture under sulfur limited conditions (Ruff et al 1999). Therefore, they presumed that the capacity to degrade these compounds extensively is widespread in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruff and co-workers showed that fourteen sulfonated aromatic compounds, five of which were sulfonated aromatic amines, were degraded by a mixed culture under sulfur limited conditions (Ruff et al 1999). Therefore, they presumed that the capacity to degrade these compounds extensively is widespread in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, these specific strains only have a narrow substrate range and therefore only a limited number of different compounds are degraded (Hooper 1991;Kertesz et al 1994;Cook et al 1998;. Also sulfonated aromatic amines can be used as a sulfur source if no other sulfur compound is present, which are unrealistic for natural and wastewater treatment environments (Zurrer et al 1987;Ruff et al 1999). Additionally, another non-biological process for the removal of sulfonated aromatic compounds is autoxidation, resulting in the formation to colored polymers (Zerbinati et al 1997;Kudlich et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the failure to obtain enrichment, seen above with LADPEDS, is unusual in our experience (A. M. Cook, unpublished data). The desulfonation products, in contrast to the sulfonates, are reactive compounds which can bind to soils, polymerize, or be subjected to biodegradation (24,26). The rationale is that the conversion of an arylsulfonate to a phenol will make the latter much more reactive and liable to attack than the former (35).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially useful with organosulfonates, because the general desulfonation of aromatic compounds yields the corresponding phenol (8), and the hydroxy analogue of a benzenesulfonate (i.e., the phenol) is generally degradable (35). Recent work indicates that a desulfonation of "recalcitrant" xenobiotic compounds could lead to their further degradation or binding to soil components (15,16,18,24,26).…”
mentioning
confidence: 99%
“…Several arylsulfonates can be desulfonated and utilized as carbon, energy and/or sulfur source by bacteria (CAIN and FARR 1968, CONTZEN et al 1996, ELSGAARD et al 2003, FEIGEL and KNACKMUSS 1993, FOCHT and WILLIAMS 1970, LOCHER et al 1989a, LOCHER et al 1989b, RUFF et al 1999, THURNHEER et al 1990, ZURRER et al 1987, and possibly by algae (LUTHER and SOEDER 1987). However, desulfonation of arylsulfonates has been reported mostly in organisms carrying out aerobic metabolism.…”
mentioning
confidence: 95%